Clinical and morphological response to neoadjuvant chemotherapy followed by chemoradiotherapy in a patient with locally advanced gastric cancer: a case report - V. Yu. Skoropad; D. Yu. Mironova; I. V. Kolobaev; T. A. Agababyan; E. S. Zhavoronkova; V. N. Grinevich; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2023)
Background. Gastric cancer is one of the most common cancers with the highest incidence and mortality rates worldwide. Gastrectomy/distal subtotal resection with D2 lymphadenectomy and perioperative chemotherapy with FLOT is the standard treatment for locally advanced gastric cancer. Currently, the role of chemoradiation therapy in the treatment of gastric cancer has not been well determined. From 2019 to 2021, a prospective phase 2 clinical trial was undertaken at A. Tsyb Medical Radiological Research Centre (MRRC) to evaluate the safety and efficacy of neoadjuvant therapy: induction chemotherapy with FLOT (2 cycles) and chemoradiotherapy (total dose of 46 Gy with the concurrent chemotherapy with capecitabine and oxaliplatin) followed by surgery. The aim of the study was to demonstrate the effectiveness of neoadjuvant therapy for locally advanced gastric cancer with a favorable pathological response, downstaging and more than 2.5-year disease-free survival. Case description. A 48 year-old male patient was admitted to the MRRC with complain of epigastric pains for 2 months. Gastroscopic biopsy revealed gastric cancer. The comprehensive examination revealed proximal gastric cancer involving the abdominal segment of the esophagus (cT3N3aM0, stage III). The patient was invited to participate in the clinical trial. The patient accepted to participate voluntarily and signed an informed consent. He received 2 cycles of FLOT chemotherapy followed by chemoradiotherapy and surgery (gastrectomy with resection of the abdominal segment of the esophagus and D2 lymph node dissection). Histological examination of the surgical specimen revealed grade 1b pathological response (Becker criteria). Histological examination of lymph nodes revealed pathological complete response. The patient is alive after 33 months of gollow-up without the evidence of disease progression. Conclusion. Neoadjuvant induction chemotherapy followed by chemoradiotherapy resulted in a favorable pathological response, downstaging and 2.5-year disease-free survival.